Peran guru PPKn dalam mengimplementasikan pendidikan karakter pada Siswa Kelas XI di SMK Bina Patria 1 Sukoharjo - Leki, Fidiayanti; Mansur, Achmad; Nurkhasan, Fajar; Suyahman, Suyahman; Srilestari, Titik (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research discusses the role of Pancasila and Citizenship Education (PPKn) teachers in implementing character education for class XI students at SMK Bina Patria 1 Sukoharjo. The research method used is a qualitative method through direct observation of subjects andobjects at SMK Bina Patria 1 Sukoharjo. The results of the research show that PPKn teachers at SMK Bina Patria 1 Sukoharjo have a strategic role in shaping students' character, involving them in moral values, cultural values and ethics in PPKn learning materials. Civics teachers also act as mentors, guiding students in developing positive attitudes such as responsibility, cooperation and discipline. This research will explore the strategies of PPKn teachers, the challenges they face and the impact of implementing character education in the vocational school environment. Therefore, it is recommended that there be collaborative efforts between teachers, schools and parents to strengthen the character of education in the educational environment of SMK Bina Patria 1 Sukoharjo.